Perspective on the new Africa Food Safety Agency - Amare Ayalew; Winta Sintayehu; Wezi Chunga-Sambo; Janet Edeme (npj Science of Food)
The recently established Africa Food Safety Agency (AfFSA) will be a Specialized Technical Institution of the African Union, tasked with coordinating and harmonizing food safety policies and regulations, while providing for centralized risk assessment capacity and food safety data hub. It will promote experience and capacity sharing across African Union Member States and international partners. AfFSA will contribute to public health, food and nutrition security, and intra-Africa and global trade in safe foods. The statutory functions of AfFSA are relevant to stakeholders within Africa and globally who in turn could play key roles to enable it successfully deliver its functions.